The current state of the veterinary drugs market in the Tyumen Region - V. V. Byshenko; О. I. Knysh; L. N. Zadirachenko; А. О. Egorova; Yu. S. Rodina (IRBIS LLC, 2022)
Objective: to assess the current state of the veterinary medical product market in the Tyumen Region.Material and methods. The objects of the study included data from the State Register of Medicinal Products for Veterinary Use for 2019-2022; veterinary pharmacy organizations and veterinary clinics in the Tyumen Region (33); price lists of veterinary pharmaceutical organizations; questionnaires of veterinary specialists (69) and consumers of medicinal products for veterinary use (93).Results. An analysis of the Register of Medicinal Products for Veterinary Use registered in the Russian Federation revealed a positive trend in the registration of new positions: with 2190 registered drugs about 300 more positions are registered annually. It was determined that the ratio of veterinary drugs of various pharmacotherapeutic groups is critically uneven (31.05% - antibacterial agents; 28% - immunobiological drugs; 0.46% - cardiovascular drugs; 0.14% - antitumor drugs). The study of the wholesale segment of the veterinary drugs market on the territory of the Tyumen Region showed that the range of wholesale trade organizations in veterinary drugs mainly consists of products for animals (at the largest one veterinary drugs account for only 16%). As a result, low indicators of the assortment are observed (breadth and completeness coefficients for pharmacotherapeutic groups), and there are problems with the availability of veterinary drugs. The analysis of the assortment of veterinary pharmaceutical organizations and clinics (retail segment of the market) revealed low breadth coefficients for medicinal products for veterinary use (median 0.09). A sociological survey showed a low level of awareness of all veterinary drugs consumer groups about the scope of their circulation.Conclusion. The study of the current state of the veterinary medicinal product market in the Tyumen Region identified the problems of their availability both in the wholesale and retail segments, which need to be addressed with the help of state regulation (including the introduction of a minimum range of drugs for veterinary use) and normalization of the assortment policy at the level of veterinary pharmacies and clinics. Because of the lack of registration for some drugs necessary for the treatment of animals, veterinarians are forced to put into practice drugs for medical use, deliberately violating the law. Given the experience of many foreign countries, we consider it expedient to allow the use (in special cases) of medical drugs in veterinary medicine. This will solve the problem of pharmacotherapy availability and allow veterinarians to provide better care to animals.